Classification of forensic psychiatric examinations - O. P. Makarova (Bulletin of Kharkiv National University of Internal Affairs, 2023)
The article considers the classification of forensic psychiatric examinations according to various criteria. The most common is the division into types depending on the subject matter of research. According to this criterion, the following types of forensic psychiatric examinations are distinguished:forensic psychiatric examination of the suspect or accused. The purpose of this examination is to establish the presence or absence of any mental disorder in the person charged with the offence that could affect his or her ability to understand and control his or her actions;forensic psychiatric examination of the witness, the purpose of which is to establish the presence or absence of any mental disorder that could affect his or her ability to perceive, remember and reproduce information during the period of time when the events about which he or she testifies took place;forensic psychiatric examination of the victim, the purpose of which is to establish the presence or absence of any mental disorder in the victim during the period of time when the events occurred that could affect his or her ability to understand the situation, assess the danger and respond adequately to it;forensic psychiatric examination of the convicted person, the purpose of which is to establish the presence or absence of a mental disorder in the convicted person, which may be the basis for applying compulsory medical measures to him/her.In addition, the types of forensic psychiatric examinations are considered:forensic psychiatric examination in cases of limitation of civil capacity of an individual, recognition of an individual as incapacitated. The purpose of this examination is to establish the presence or absence of a mental disorder in an individual that prevents him or her from fully understanding the significance of his or her actions and controlling them;forensic psychiatric examination in cases of invalidation of a transaction. The purpose of this examination is to determine whether a person had a mental disorder at the time of the transaction that could have affected his or her ability to understand the meaning of the transaction and control his or her actions.